Evaluating Relationship Between Islamic Store Image and Malay Muslim Consumer Attitudes’ in Patronizing a Store - Waida Irani Mohd fauzi; Nazlina Zakaria; Sany Sanuri mohd Mokhtar; Rushamie Zainn Yusoff; Maha Yusr (International Journal of Supply Chain Management, 2018)
The growing of religious consciousness among Muslim consumers is become an introductory factor for the new concept of businesses that concern with religious values expand in the market. Retailer must realize that Muslim consumer must be treat as a niche market for the reason that, they have their own evaluation in patronizing a stores. The effect of Islamic lifestyles in the marketing environment had urge retailer to complement their marketing strategy to be suit with Islamic attributes. The religiosity adherence among Muslim consumers may affect the patronage behavior of the store. With the changing behavior among Muslim consumer, thus, this study intends to examine the influence of Islamic store image on Muslim consumer attitudes. The study was done in several states of Malaysia by cluster sampling. A number of customers were asked to complete the questionnaires by mall intercept method. Finding of the study found that, Islamic store image have a significant impact to the patronage behavior of the Muslim consumer in patronizing a store in Malaysia. As a conclusion for this study, Islamic image of the store significantly become major determinant towards Muslim customer in patronizing a store. Customer feel more confident by considering store image as it give a first impression towards the expectation of the halal status.